Anaysis of Arabic Textbooks in Character Education Curriculum Framework K13 - Munasib, Munasib; Faoziyah, Laila (Language Development Center, 2023)
Background: Textbooks are books that contain knowledge that is the result of an analysis of the curriculum in written form to achieve the desired learning objectives. However, in several textbooks, problems were found that the contents of the books were not following the curriculum content standards and textbook standards. Therefore, it is necessary to analyze the contents of Arabic textbooks. Purpose: This research is to analyze the Arabic language textbooks of Madrasah Aliyah based on the K13 character education framework. Method: The method used in this study is a literature study. As for data analysis, the authors used content analysis techniques based on the realm of spiritual attitudes, the realm of social attitudes, the realm of knowledge, and the realm of skills as stated in the 2013 curriculum. Results and Discussion: The results of the analysis of the qira'ah material Chapter II Arabic language textbooks for class XI Madrasah Aliyah in odd semesters show that in the material entitled al hayah as shihiyyah there is knowledge value in the form of scientific integration. Skill value, students have skills in combining knowledge between health sciences and Islamic religious knowledge. The value of a spiritual attitude, namely being good at being grateful, and a social attitude, namely by maintaining, setting an example, and inviting others to always apply a healthy lifestyle in life. Conclusions and Implications: Arabic textbook by H.D. Hidayat class XI is following the Core Competencies and Basic Competencies formulated in the 2013 General Curriculum. The implications of the results of this analysis are in the form of interpretations that can be used as additional explanations in learning Arabic.